Methodology for Determining the Coefficient of Relative Importance of Economic Indicators of Enterprises During Restructuring Under the Influence of Crisis Phenomena - Azzam, Berdikulov; Yunusovich, Siddikov Mumin (European Journal of Life Safety and Stability (2660-9630), 2022)
This article develops a methodology for determining the coefficient of relative importance of economic indicators of enterprises in the process of reconstruction under the influence of crisis events, and recommendations on the impact on the activities of the enterprise were previously asked.